Sliding mode control technique of step down converter using reaching law - Ningappa, Sridhara Somaguddu; Basavarajan, Siddesh Kondapur; Katappa, Sudharashan Mungasavalli; Ramareddy, Sandeep Velur; Basavarajappa, Lavakumar Tavane; Sutikno, Tole (Institute of Advanced Engineering and Science, 2023)
The robust reaching law based sliding mode control is used for chattering suppression, minimization of steady state error and reaching speed kept minimized. With fine tuning of parameters of robust reaching law, the sliding mode reaches the equilibrium point at the earliest. The stability of the proposed reaching law is analyzed. In one hand, they guarantee the system reach the sliding face rapidly and stay on it, in another way they decline the chattering effectively, even unmatched certainties and disturbances. Such that the system response can better realize the unification of rapidity. A proposed reaching law ia analyzed mathematically and applied to SMC DC-DC buck converter to lessen the chattering, because switching devices are existing in the model, it reduces effectively in the switching losses in the switching devices of the dc-dc converter. In turn effectiveness of the efficiency increases. MATLAB/Simulink results give significant decline of chattering and switching losses in the buck converter.